Output and Substitution Elasticities in Pakistan’s Industrial Sectors: Panel Data Analysis - Nazir, Sidra; Mahmood, Nasir; Hameed, Gulnaz (The Economics and Finance Letters, 2022)
This study performed a panel data analysis of Pakistan’s nine major sub-industries in the years 1980–2019. The primary objective was to conduct a disaggregate analysis of the substitution elasticity of inputs in the different industries, including textile, mining and currying, manufacturing, fuel extraction, electricity, gas, and water supply, using the translog production function. The study used the translog production function to estimate output and substitution elasticities for each sub-industry. Based on the results of the output elasticities, the study concluded that there were negative elasticities for the inputs oil, gas, and labor, except for capital, which had positive elasticity, causing increasing returns to scale for industries. The elasticity of substitution was greater than one and the value was positive, showing that costly energy inputs can and should be replaced with cheaper energy inputs in these industries. For instance, electricity can be replaced with gas, which is cheaper than electricity in Pakistan.